Cardiac Aspergilloma: A Rare Case of a Cardiac Mass Involving the Native Tricuspid Valve, Right Atrium, and Right Ventricle in an Immunocompromised Patient - Christina S. Chen-Milhone; Kalyan Chakravarthy Potu; Sudhir Mungee (Case Reports in Cardiology)
Aspergillus can cause devastating opportunistic infections in immunocompromised patients. Rarely does this fungus invade the heart, and when it does, survival is especially poor despite optimal medical and surgical treatment. We report a case of cardiac aspergilloma with involvement of the tricuspid valve and both the right atrium and ventricle found on a transthoracic echocardiogram in an immunocompromised patient after developing atrial fibrillation with rapid ventricular rate. The findings from this case suggest that early clinical suspicion is critical in early diagnosis and thus early treatment.